PERANCANGAN ALAT MONITORING TEGANGAN DAN ARUS LISTRIK BERBASIS MIKROKONTROLER ARDUINO UNTUK RUMAH - Erick Radwitya; Syarif Ishak Alkadri (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2026)
The increasing household electricity consumption drives the need for effective monitoring systems to optimize energy usage and enhance electrical installation safety. This research develops a prototype monitoring device based on an Arduino Mega 2560 microcontroller, integrated with a ZMPT101B voltage sensor and an ACS712-30A current sensor, to measure electrical parameters in real time. The research methodology employs a quantitative experimental approach with stages including hardware design, firmware development, sensor calibration, and accuracy validation using standard measuring instruments. The system features a 20x4 LCD interface for local display and an ESP8266 module for transmitting data to the Blynk platform, enabling remote monitoring via a mobile application. Testing results demonstrate excellent accuracy, with Mean Absolute Percentage Errors of 0.69% for voltage, 1.66% for current, and 1.76% for active power. System response time reaches 87 milliseconds with data transmission latency of 1.45 seconds, meeting real-time monitoring standards. The notification system successfully detects overvoltage and overcurrent conditions with 99% reliability and an average response time of 92 milliseconds. Testing across various load types shows optimal performance at a power factor above 0.85. This system offers a cost-effective solution to improve energy efficiency and the safety of household electrical installations, with an affordable implementation cost. Keywords: ACS712 sensor, Arduino, Energy Monitoring, Internet of Things, ZMPT101B sensor